Analisis Pengukuran Beban Kerja Mental dan Fisik dengan Kinerja Karyawan Menggunakan Metode Nasa Task Load Index (Nasa – TLX) pada Departemen Manufaktur di PT. Petnesia Resindo - Indah Rizky Mahfira; Andres Andres (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
PT. Petnesia Resindo is a manufacturing company in the field of the chemical industry that produces PET Resin products with the most employees have a more dominant thinking activity compared with physical activity. Since it was founded, PT. Petnesia Resindo've never measured the level of workload and performance achieved. Therefore, this study aims to measure the workload and performance that has been achieved by the employees in the Manufacture Department of PT. Petnesia Resindo as well as the relationship of both. There are two models of research, the first model is the relationship indicators workload performance with employees and the second model is relationships with workload indicators performance assessment of employees. To know the magnitude of the workload of the employees in the Manufacture Department of PT. Petnesia Resindo, performed the measurement method using NASA TLX with 6 size dimensions there are Mental Demand, Physical Demand, Temporal Demand, Performance, Frustation and Effort. Based on the score obtained, noted that 32% of employees have a high workload and a 68% are very high. As for knowing the performance use the Rating Scale with Likert scale. From the results of the measurements, it is known that 7% of employees have a good enough performance and 90% are bad. The research of the model is formed, it brings that both variables have no significant relationship but the company requires the addition of employees a number of 91 people in order to reduce the high level of workload and as proposed in this research.